ANALYSIS OF THE EXISTENCE OF ELEMENTS OF GHARAR AND TADLIS IN MEMBER CARD OPERATIONS IN BUYING AND SELLING - Putroe Salsabila Mauza (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2018)
Rabbani Banda Aceh branch is one of the companies engaged in fashion that implements a membership shopping system or member card. In its implementation, consumers who want to become members are required to pay an initial registration fee and must also pay for the extension of the member card when the period has expired. This kind of transaction will be very vulnerable to elements that are prohibited in muamalah. The purpose of this study is to determine how the operations and workings of the member card Rabbani Banda Aceh and also the validity of the Rabbani member card operations in terms of the existence of elements of gharar and tadlīs. The research method used is descriptive analysis, data obtained from interviews, documentation and literature studies. From the results of the study it was found that the operational practice of member cards, participants must pay a registration fee of Rp.50,000 for global members and Rp.10,000 for student members and will get a 10% discount on every purchase valid for one year. Members must pay Rp.25,000 to extend their card. In terms of the elements of gharar and tadlīs, the practice of using member cards at Rabbani does not contain the element of tadlīs, but there is an element of gharar in additional fees when extending member cards. The element of gharar in the implementation of member cards at Rabbani Banda Aceh occurs in the limitation of student member discounts which are only discounted on headscarves and also the lack of clarity of discount information outside members which is not known by consumers of member cards so that members cannot take advantage of their members.